The Influence of ancient Turkic civilization on traditional Chinese culture - Massimkhanuly, D.; Abidenkyzy, A. (Journal of Oriental Studies, 2021)
Part of the lands inhabited by ancient Turkic peoples today belong to the territory of the People’s Republic of China. For centuries BC, the Turkic tribes in Central Asia fought each other to become a unified state and fought for the creation of a state. The historical circumstances mentioned were widely spread in the dynastic chronicles of China, were included in written sources, in the writings of travelers and historical originals of the Muslim world, all this led to the development of relations between the Chinese and Turkic peoples. The study of the history of the ancient Turkic peoples by Chinese researchers is of great scientific importance. For example, in the official Chinese chronicle “twenty-four stories”, written in different eras, data related to the ancient Turks were translated from Chinese into modern Kazakh and subjected to scientific revision. This is one of the unique sources directly related to the Turkic history. Since ancient times, it has become obvious in the history of science that the Turkicspeaking peoples contributed to the development of relations between the West and the East, as well as developed bilateral relations. In the Chinese chronicle, the Turks were called the descendants of the Huns. The word “Turks” was used only in reference to the representatives of the ruling aristocratic family among the Turkic-speaking nomads. In later times, the Turki acquired political significance, as other tribes under their rule began to be called them. In this context, this article examines the influence of the Ancient Turkic language on traditional Chinese culture in the fields of language, literature, music, dance, household and industrial equipment, and religion. Key words: Turkic, Chinese, civilization, tradition, culture, ancient Turkic civilization, traditional Chinese culture.